2013
DOI: 10.12681/mms.350
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and ecomorphology of three clupeoids in the N Aegean Sea

Abstract: This study examines the feeding habits of anchovy (Engraulis encrasicolus), sardine (Sardina pilchardus) and round sardinella (Sardinella aurita). The results are combined with previously published information on feeding-related morphological features (i.e. mouth area, intestine length and tail area) in order to explore morphological affinities between species and the effect of ecomorphology on their co-existence. These species were mainly zooplanktivorous and no dietary differences were found with sex and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
3
16
1
Order By: Relevance
“…reported in the GoL byPethybridge et al (2014), or byKarachle and Stergiou (2014) in another area of the Mediterranean Sea (Agean Sea), suggesting that the contaminant variations we found are probably not related to differing diets. Other factors such as substantial contaminant elimination through reproduction (i.e.…”
supporting
confidence: 60%
“…reported in the GoL byPethybridge et al (2014), or byKarachle and Stergiou (2014) in another area of the Mediterranean Sea (Agean Sea), suggesting that the contaminant variations we found are probably not related to differing diets. Other factors such as substantial contaminant elimination through reproduction (i.e.…”
supporting
confidence: 60%
“…That is, the fish that are high on the trophic level might be expected to concentrate higher levels of bioaccumulative metals as Hg and the same was found in this study for swordfish and bluefin tuna, typical high-order marine predators. In the same way, in accordance with feeding spectra, anchovies and sardines feeding mainly on water plants and plankton (Karachle & Stergiou 2014) contained significantly lower levels of Hg (p = 0.05) than fish as European conger eel, long-nose skate, common sole and black belly rosefish, whose diet consisting largely of fishes (Stergiou & Karpouzi 2002) reflected a major metal content. Moreover, the low levels observed in anchovies and sardines could also be habitat effect, they being surface feeders and, thus, exposed to lower contamination levels than demersal and benthic counterparts (Storelli et al 2006).…”
Section: Metals In Fishery Productsmentioning
confidence: 52%
“…A recent study based on a combined analysis of ecomorphology and trophic position showed that sardine and sardinella from the North Agean Sea have a greater resemblance and exploit the same food resources differently (Karachle and Stergiou, ). In the Mauritanian waters, sardine and sardinella feed mainly on phytoplankton, copepods and detritus (Gushchin and Corten, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to switch between these feeding modes makes this species highly opportunistic, being able to maximize its energy intake by employing the most appropriate feeding mode for a particular food environment. In addition, sardine had a shorter intestine compared to that of sardinella and displays a more protractile mouth that might be more advantageous in the case of particulate feeding (Karachle and Stergiou, ). Species with lengthier guts achieve optimum nutrient and energy gain from the food consumed suggesting that sardinella is more efficient than a sardine in terms of energy gain from the food consumed.…”
Section: Discussionmentioning
confidence: 99%